1992
DOI: 10.1111/j.1365-2621.1992.tb14318.x
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Maturation of Cheddar Cheese: Influence of Added Lactobacilli and Commercial Protease on Composition and Texture

Abstract: The addition of live and heat-shocked Lactobacillus casei-casei L2A and Neutrase" was tested for its ability to accelerate the maturation of Cheddar cheese. An evaluation of physicochemical and rheological properties showed that cheese pH was decreased by bacterial and enzymatic additives, while fracturability and cohesiveness were influenced principally by Neutrase. The integrated process recommended is composed of three parts: first, the addition of live L. casei-casei L2A to control the undesirable microflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…Ripening is a relatively expensive process for the cheese industry; therefore, reduction of this period without destroying the quality of matured cheese has economic and technological advantages (Trépanier et al, 1992b;Fox et al, 1998): (i) savings in refrigeration, labor and inventory expenses; (ii) increased cheese production in developing countries where investments in storage facilities can be a limiting factor; and (iii) rapid production of cheese flavor.…”
Section: Acceleration Of Cheese Ripeningmentioning
confidence: 98%
“…Ripening is a relatively expensive process for the cheese industry; therefore, reduction of this period without destroying the quality of matured cheese has economic and technological advantages (Trépanier et al, 1992b;Fox et al, 1998): (i) savings in refrigeration, labor and inventory expenses; (ii) increased cheese production in developing countries where investments in storage facilities can be a limiting factor; and (iii) rapid production of cheese flavor.…”
Section: Acceleration Of Cheese Ripeningmentioning
confidence: 98%
“…Several authors have studied the effect of addition of adjunct strains of mesophilic lactobacilli to cheese milk. This approach was used to relate changes in cheese flavour and quality observed during ripening to growth of lactobacilli, or other adventitious flora, such as micrococci, which can also be present in raw milk cheeses, and to identify starters capable of accelerating ripening and improving cheese quality (Reiter et al 1967; Law et al 1976; Lemieux et al 1989; Purchades et al 1989; Broome et al 1990; Lee et al 1990; Trepanier et al 1991, 1992; McSweeney et al 1994; Lynch et al 1996; Swearingen et al 2001). Generally, the use of mesophilic adjunct Lactobacillus cultures increases the level of free amino acids and improves the flavour characteristics of Cheddar cheese, but on some occasions, adjunct lactobacilli have been associated with flavour defects.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports showed that the moisture, protein, and fat contents of Cheddar cheese were in ranges of 34-38%, 22-25%, and -38%, respectively (18,19).…”
Section: Resultsmentioning
confidence: 98%